The Use of Cooperative Integrated Reading and Composition (CIRC) Method in Improving Writing Ability of Narrative Text of the Second Year Students of SMAN 4 Pekanbaru Desi Nurista, - Desi Nurista; Rumiri '; Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This classroom action research was aimed to find out if the use ofCooperative Integrated Reading and Composition (CIRC) Method could improve thewriting ability of the second year students of SMAN 4 Pekanbaru. The participants were31 students. The procedures applied were: (a) dividing students into pairs, (b) askingstudents to read to each other the story, (c) asking students to correct their teammates’error, (d) asking students to answer the questions related to the story in team, (e) askingstudents to pronounce the difficult words listing, (f) asking students to find the meaningof the difficult words listing, (g) asking students to write a draft composition ofnarrative texts related to the passage, (h) asking students to edit one’s another’s workby using peer editing, (i) asking students to finish their writing based on theirteammates’ revision. The data was collected by using of tests, observation sheets, andfield notes. The level of achievement in this research was 85, based on the standardminimum criteria of achievement of English subject in SMAN 4 Pekanbaru. Theresearch finding showed that the implementation of applying CIRC as the teachingmethod could improve students’ writing ability both at the first, second, and third cycle.Based on the data analysis that is obtained, the students’ score was improve from 60,32in the pre-test, to 74,62 in post-test 1, to 83,29 in post-test 2, and up to 87,68 in post-test3. Therefore, the implementation of CIRC method could improve students’ writingability of the second year students of SMAN 4 Pekanbaru.Keywords: CIRC Method , Writing Ability, Narrative Text